Efektivitas Program Jaminan Kesehatan Nasional (JKN) bagi Warga Miskin - Lina Sahida Br Sinaga; Kayla Dwi Saputri; Julika Putri; Wahjoe Pangestoeti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The National Health Insurance (JKN) program is a strategic initiative by the Indonesian government to ensure accessible and affordable healthcare for all citizens. Based on literature review and analysis of secondary data, the JKN program significantly contributes to reducing direct household health expenditures (Out-of-Pocket/OOP), particularly among low-income and vulnerable populations. However, several challenges remain, including additional outlays for uncovered services such as non-generic medications and inpatient class upgrades, as well as limitations in health infrastructure. Furthermore, the integration of digital technology through the JKN Mobile application demonstrates a high level of effectiveness in administrative efficiency and user participation. This platform has expanded healthcare accessibility and improved user satisfaction, although digital literacy and technological disparities persist. Hence, strengthening technology-based policies and conducting regular evaluations are essential for ensuring the sustainability and equity of the JKN program implementation.